A Forgery Of Fate - Lim, Elizabeth (New York : Alfred A. Knopf, 2025)
"A girl who paints the future and a cursed dragon lord, bound by love and deception, pair up in a plot to bring down the gods"--.
new ya book 2025 summer.
Ages 12 and up.
Keywords: Fantasy; Romance stories; Swindlers and swindling -- Fiction; Dragons -- Fiction; Novels; Romance fiction; Fantasy fiction